2006
DOI: 10.1016/j.febslet.2006.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Detecting transient protein–protein interactions by X‐ray absorption spectroscopy: The cytochrome c6‐photosystem I complex

Abstract: Reliable analysis of the functionality of metalloproteins demands a highly accurate description of both the redox state and geometry of the metal centre, not only in the isolated metalloprotein but also in the transient complex with its target. Here, we demonstrate that the transient interaction between soluble cytochrome c 6 and membrane-embedded photosystem I involves subtle changes in the heme iron, as inferred by X-ray absorption spectroscopy (XAS). A slight shift to lower energies of the absorption edge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(36 reference statements)
1
10
1
1
Order By: Relevance
“…As the reducing electron is not located in these orbitals, such subtle changes may have little influence on the redox potential. This situation is clearly different to that previously reported for cytochrome c 6 , which shows a perturbation on the pre-edge region corresponding to its oxidized species, instead of the reduced ones, upon binding its reaction partner, photosystem I (Díaz-Moreno et al 2006). In such case the pre-edge corresponds to transfer to a half-occupied non-bonding d orbital, which is that receiving the reducing electron, so the observed changes can be correlated with changes in the redox potential of the heme protein.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…As the reducing electron is not located in these orbitals, such subtle changes may have little influence on the redox potential. This situation is clearly different to that previously reported for cytochrome c 6 , which shows a perturbation on the pre-edge region corresponding to its oxidized species, instead of the reduced ones, upon binding its reaction partner, photosystem I (Díaz-Moreno et al 2006). In such case the pre-edge corresponds to transfer to a half-occupied non-bonding d orbital, which is that receiving the reducing electron, so the observed changes can be correlated with changes in the redox potential of the heme protein.…”
Section: Resultscontrasting
confidence: 99%
“…1 eV below that of C f III , as previously found for the reduced and oxidized states of two closely related proteins, as heart cytochrome c (Cheng et al 1999) and Nostoc cytochrome c 6 (Díaz-Moreno et al 2006). In case of cytochrome c (Cheng et al 1999), photoreduction of the oxidized species was observed only after the 16th spectrum of the series.…”
Section: Resultssupporting
confidence: 77%
“…For comparison with biomolecules we add Fe 2p and N 1s spectra for cytochrome c, a metalloprotein that plays a role in reducing photo-oxidized donors in lipid membranes. 12,23 To our knowledge only the much broader Fe 1s edge has been reported for cytochrome c. [51][52][53][54][55] While fingerprinting methods provide quick information about the oxidation state from the raw data, there is a lot more to be learned from proper theoretical modeling, as discussed in Sec. II B.…”
Section: Transition Metal 2p Edgesmentioning
confidence: 97%
“…Likewise, metal ions can mediate or trigger protein–protein interactions, as already pointed out [28]. In redox proteins, however, minor changes in the metal environment are associated with transient binding, although, in some cases, they could play a physiological role [34,35].…”
Section: Interactions Involving Metalloproteinsmentioning
confidence: 99%